Factors Contributing to Nursing Students' Lack of Interest in Clinical Placement: A Case of Jamshoro (Pakistan) (Journal of Asian Development Studies, 2024)
Clinical placements serve as a vital educational experience, allowing undergraduate and postgraduate nursing students to integrate theoretical knowledge with practical application in real-world settings. Clinical placement has a significant impact on the attitude, knowledge, skills, and problem-solving abilities of students. This study aimed to determine the factors related to the nursing students’ lack of interest in clinical placement. A quantitative cross-sectional study was utilized to determining the factors contributing to nursing students' lack of interest in clinical placements was conducted at Peoples Nursing School, Jamshoro. Stratified random sample of (n=125) and Rao software was utilized to determine the sample size, employing a 95% confidence interval and a 5% margin of error. The survey instrument was adapted and modified with expert, the collected information was subsequently analyzed utilizing IBM SPSS software, version 25. The major findings of this study were revealed that two third 72% of participants were female and 88.8% were unmarried, indicating a predominantly young and single student population, also more than 71% nursing students were belonging to rural areas. Meanwhile more than two third participants agreed with inadequate resources, more than fifty percent strongly agreed with being stipend not given. Overall, the data suggest that the majority of the nursing students expressed lack of interest while on clinical placement due to various factors were determined. We recommend that improving clinical teaching, early identifying factors, and reduce shortage of clinical facilitates can develop interest among learners.